800 nm near-infrared light-excitable intense green-emitting Li(Gd,Y)F-4: Yb,Er-based core/shell/shell upconversion nanophosphors for efficient liver cancer cell imaging - Choi, Jung Eun; Kim, Hee-Kwon; Kim, Youngsun; Kim, Gayoung; Lee, Tae Sup; Kim, Sehoon; Kim, Donghwan; Jang, Ho Seong (Elsevier BV, 2020)
In this study, novel 800 nm-excitable and highly intense green-emitting non-NaY(Gd)F-4-based core/shell/shell (CSS) upconversion nanophosphors (UCNPs) are reported. Scheelite-structured Li(Gd,Y)F-4:Yb,Er core UCNPs are synthesized, followed by the formation of a Nd3+-doped active shell and inert shell, and the novel Li(Gd,Y) F-4:Yb,Er/LiYF4:Nd,Yb/LiGdF4 CSS UCNPs are applied to liver cancer cell-targeted upconversion luminescence imaging. X-ray diffraction and electron energy loss spectroscopy confirm that single tetragonal phase scheelite-structured CSS UCNPs are successfully synthesized. Because of the formation of the active shell and inert shell on the core, CSS UCNPs display bright green light under both 800 and 980 nm excitations. In particular, the synthesized CSS UCNPs exhibit a high absolute upconversion quantum yield of 0.15% under 800 nm excitation. For liver cancer cell targeting, free amine and poly(ethylene glycol) (PEG)-introduced glycyrrhetinic acid (GA) (GA-PEG-NH2) is synthesized, and the GA-PEG-NH2 is conjugated with the CSS UCNPs, whose surface was modified with poly(acrylic acid sodium salt). HepG2 liver cancer cells are imaged with the GA-PEG-NH2-conjugated CSS UCNPs and an 808 nm near-infrared laser, and in vivo liver cancer cell imaging is successfully conducted. (c) 2020 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: ALGINATE NANOPARTICLES; PHOTODYNAMIC THERAPY; FACILE SYNTHESIS; NANOCRYSTALS; LUMINESCENCE; EMISSION; RED; DOXORUBICIN; ENHANCEMENT; RELEASE